Methods for Reinforcing Communicative Tasks through Role-Playing Games (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Role-playing games have become an effective pedagogical approach for strengthening communicative tasks in language classrooms. This paper explores the methods and strategies for integrating role-play into English language teaching to enhance learners’ fluency, interaction, and communicicative competence. Drawing upon classroom practices and theoretical insights, the study emphasizes how role-playing activities create authentic, learner-centered contexts that foster creativity, critical thinking, and confidence. By simulating real-life communication scenarios, role-playing not only develops linguistic skills but also nurtures sociolinguistic awareness and intercultural understanding. The findings suggest that when effectively implemented, role-playing serves as a powerful tool for reinforcing communicative tasks, encouraging learners to express themselves meaningfully while collaborating with their peers in dynamic and motivating situations.